Evaluation of Sustainable Development in Mathura - Vrindavan: A Critical Analysis - Naumi Garg, Ar.; Singla, (Ar.) Atul; Singla, (Ar.) Atul; Jain, Ar.Shilpa; Deb, Ar.Anisha (Journal of Neonatal Surgery, 2025)
The belief in lord Krishna and the religious significance of Mathura Vrindavan has attracted a growing number of tourists in recent years. However, the rapid influx of religious tourists and urbanization poses multiple challenges. Though Government of India (GOI) has introduced various missions and schemes like HRIDAY (Heritage City Development and Augmentation Yojana), AMRUT (Atal Mission for Rejuvenation and Urban Transformation), PRASHAD (Pilgrimage Rejuvenation and Spiritual Heritage Augmentation Drive), and Smart Cities Mission in 2015 to ensure sustainable and heritage-inclusive development of the pilgrimage cities of India. It is important to analyse the recent development in the city under the above schemes for its sustainability and heritage inclusiveness. The United Nations laid out 17 Sustainable Goals in 2015 UNSDG 11 is Sustainable Cities and Communities. NITI Aayog has laid down the Indian version of UNSDGs. This study includes the impact of recent development on the residents and evaluates its feasibility for achieving sustainable development goal 11. It examines the existing policies, identifying gaps and providing practical recommendations for policymakers for social, economic, environmental, and cultural sustainability to balance the preservation of religious heritage in Mathura Vrindavan